Women Fight, Women Write : Texts on the Algerian War - Mortimer, Mildred P. (Book collections on Project MUSE., 2018)
"This book examines Algerian women's narratives of the Algerian War of Independence, drawing on political and historical analyses, interviews, memoirs, fiction, poetry, essays, and films"--